2009
DOI: 10.1016/j.expneurol.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Translocator protein (18 kDa) TSPO: An emerging therapeutic target in neurotrauma

Abstract: Traumatic brain injury (TBI) induces physical, cognitive, and psychosocial deficits that affect millions of patients. TBI activates numerous cellular mechanisms and molecular cascades that produce detrimental outcomes, including neuronal death and loss of function. The mitochondrion is one of the major targets of TBI, as seen by increased mitochondrial activity in activated and proliferating microglia (due to high energy requirements and/or calcium overload) as well as increased reactive oxygen species, change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 61 publications
2
140
0
4
Order By: Relevance
“…These results confirm the reliability of the translocator protein (Papadopoulos & Lecanu, 2009) in early diagnostics of antigen-specific neuroinflammation and eventuallyof MS.…”
Section: Autoradiography and Immunochemistry Correlation With The Uprsupporting
confidence: 79%
“…These results confirm the reliability of the translocator protein (Papadopoulos & Lecanu, 2009) in early diagnostics of antigen-specific neuroinflammation and eventuallyof MS.…”
Section: Autoradiography and Immunochemistry Correlation With The Uprsupporting
confidence: 79%
“…It cannot, however, be ruled out that treatment with benzodiazepines affected the expression of the PBR. Most studies on benzodiazepines and other PBR ligands, such as Ro5-4864 and PK11195, indicate the neuroprotective effects of these ligands (35). Wilms et al (36) have shown that midazolam, clonazepam, and diazepam interfered with the in vitro synthesis and release of proinflammatory cytokines by microglia cells.…”
Section: Discussionmentioning
confidence: 99%
“…Esta se localiza a nivel de las membranas mitocondriales de distintos tipos celulares (25). El nombre de TSPO fue adoptado en el 2006 debido a nuevos hallazgos relacionados con su estructura y función molecular (24).…”
Section: Proteína Translocadora Mitocondrial (Tspo) 18 Kdaunclassified